Predicting Source Populations of Vagrants Using Breeding Population Data: A Case Study of the Lesser Black-Backed Gull (Larus fuscus) - Zawadzki, Lucinda C.; Hallgrimsson, Gunnar T.; Veit, Richard R.; Rasmussen, Lars M.; Boertmann, David; Gillies, Natasha; Guilford, Tim (Frontiers in Ecology and Evolution, 2021)
Vagrancy is critical in facilitating range expansion and colonization through exploration and occupation of potentially suitable habitat. Uncovering origins of vagrants will help us better understand not only species-specific vagrant movements, but how the dynamics of a naturally-growing population influence vagrancy, and potentially lead to range expansion. Under the premise that occurrence of vagrants is linked to increasing population growth in the core of the breeding range, we assessed the use of breeding population survey data to predict source populations of vagrants. Lesser Black-backed Gulls (Larus fuscus) served as our focal species due to their dramatic and well-documented history of vagrancy to North America in the last 30 years. We related annual occurrence of vagrants to indices of breeding population size and growth rate of breeding populations. Our idea is that the fastest growing population is the most likely source of recent vagrants to North America. Our study shows that it is possible to predict potential source populations of vagrants with breeding population data, but breeding surveys require increased standardization across years to improve models. For the Lesser Black-backed Gull, Iceland’s breeding population likely influenced vagrancy during the early years of colonization, but the major increase in vagrants occurred during a period of growth of Greenland’s population, suggesting that Greenland is the source population of the most recent pulse of vagrant Lesser Black-backed Gulls to North America.